PENGARUH TINGKAT SUKU BUNGA, INFLASI, KURS DAN PERTUMBUHAN PRODUK DOMESTIK BRUTO TERHADAP INDEKS HARGA SAHAM GABUNGAN DI BURSA EFEK INDONESIA - Tsoraya Utami; Murtala Murtala; Hilmi Hilmi (J-MIND (Jurnal Manajemen Indonesia), 2021)
ABSTRACT This study aims to examine the effect of interest rates, inflation, exchange rates and gross domestic product growth on the Composite Stock Price Index (IHSG) on the IDX during the 2003-2018 period on a quarterly basis. The type of data used is secondary data in the form of time series data obtained from published reports from Bank Indonesia, the Central Bureau of Statistics and the Indonesia Stock Exchange. The data analysis method used is the Autoregressive Distributed Lag (ARDL) Model. The results of this study found that the exchange rate and inflation had a negative and significant effect on the IHSG, while GDP growth had a positive and significant effect on the IHSG. However, the interest rate did not have a significant effect on the IHSG. Keywords:         Interest Rate, Inflation, Exchange Rate, GDP Growth and IHSG